2022
DOI: 10.11591/ijphs.v11i4.21691
|View full text |Cite
|
Sign up to set email alerts
|

Secure relationship does not mean satisfying relationship during the pandemic: The role of mattering and life satisfaction

Abstract: Relationship satisfaction (RS) is one of the major components of mental health that is often ignored due to cultural reasons. Moreover, numerous studies had indicated that when individuals have insecure attachment styles (insecurity in loving someone else), they would never develop any RS with anyone, including friends, spouses, parents, children, and relatives. The coronavirus disease 2019 (COVID-19) pandemic had triggered different social patterns among individuals all over the world, and studies during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…This sense of mattering is also positively associated with one's unconditional self-acceptance [14] positive emotion [15], and life satisfaction. Furthermore, it was reported that the sense of mattering is a significant predictor of relationship satisfaction [16], and this relationship is partially mediated by life satisfaction. The mediation relationship is also moderated by the secure attachment style, as individuals with low-to-moderate secure attachment style are more likely to be satisfied with their relationship when they feel they matter enough to their spouses.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This sense of mattering is also positively associated with one's unconditional self-acceptance [14] positive emotion [15], and life satisfaction. Furthermore, it was reported that the sense of mattering is a significant predictor of relationship satisfaction [16], and this relationship is partially mediated by life satisfaction. The mediation relationship is also moderated by the secure attachment style, as individuals with low-to-moderate secure attachment style are more likely to be satisfied with their relationship when they feel they matter enough to their spouses.…”
Section: Introductionmentioning
confidence: 98%
“…Contextually, the sense of mattering to one's partner is crucial for maintaining relationship satisfaction [13] as it is positively associated with unconditional self-acceptance [14], positive emotion [15], and overall life satisfaction. The mediation relationship between the sense of mattering and relationship satisfaction is moderated by secure attachment style, whereby individuals with low-to-moderate secure attachment style tend to be more satisfied with their relationship when they feel they matter enough to their spouses [16]. When attachment to one's spouse is secured, individuals tend to be more satisfied with their life, and in turn, more satisfied with their relationship (18).…”
Section: Introductionmentioning
confidence: 99%